Influence of proline rich peptides on the dipeptidyl peptidase IV and adenosine deaminase activities during cyclophosphamide induced immunodeficiency in rats - Antonyan, A. A.; S. S. Mardanyan; S. G. Sharoyan; H. A. Harutyunyan; Ye. G. Sargissova; N. A. Andreasyan; Galoyan, A. A. (ՀՀ ԳԱԱ հրատ.)
In in vivo experiments, it was shown that the dynamics of dipeptidyl peptidase IV (DPPIV) and adenosine deaminase (ADA1) activities in blood plasma of rats after injection of 10 and 25 mg cyclophosphamide (CPA) is similar to the dynamics of the number of lymphocytes reported in the scientific publications: In vivo փորձերում ցույց է տրվել, որ 10 և 25 մգ/կենդանուն ցիկլոֆոսֆամիդ (CPA) ներարկելուց հետո առնետների արյան պլազմայում դիպեպտիդիլպեպտիդազ IV-ի (DPPIV) և ադենոզինդեամինազ 1-ի (ADA1) ակտիվության դինամիկան նման է գիտական հրապարակումներում նկարագրած լիմֆոցիտների թվաքանակի դինամիկային, 4-7-րդ օրերին ֆերմենտների ակտիվությունը նվազում է մինչև սկզբնական ակտիվության ~ 50% և վերականգնվում են 10-12-րդ օրերին: В опытах in vivo показано, что после введения циклофосфамида (CPA) в дозах 10 и 25 мг на животное, динамика активности дипептидил пептидазы DPPIV и аденозиндезаминазы ADA1 в плазме крови крыс подобна динамике числа лимфоцитов, описанной в ряде научных публикаций: На 4-7-й дни активность ферментов падала до ~ 50% начальной активности и восстанавливалась до начальной на 10-12-й дни.
Keywords: Biology; Biochemistry; Physiology